Politics of asylum : sovereign considerations in the multilateral and humanitarian practices of refugee protection in post-apartheid South Africa - Oduba, Victor (Rhodes University, Faculty of Humanities, Department of Political Studies, 2003)
Most scholars claim that international human rights norms embodied in formal international declarations and treaties have an important impact on domestic political interests and governmental practices. This reasoning about the impact of global human rights is often applied to the post-apartheid South African immigration and refugee policies. While I acknowledge that the ratification of United Nations Conventions on refugees has altered the traditional sovereignty considerations of South Africa towards asylum seekers, I take issue with the claims that South African refugee and asylum policies are primarily motivated and based on humanitarian considerations. Instead, I argue that these policies are based on sovereign considerations and strategic foreign policy interests. As a result this sovereign interests of South Africa to study has sought to demonstrate that largely explain decisions on the part accept or reject refugees. Although norms diffusion, international advocacy networks, and prestige factors have made a big impact, in practice the refugee policy has continued to reflect South Africa's strategic interests and domestic considerations at all levels. However, I have not argued that South Africa should overlook its national and foreign interests and abide by international human rights norms regardless of the cost of doing so. I have only sought to demonstrate that refugee protection is more when powerful national interests find it conducive to manage the destabilizing refugee flows.
Keywords: Refugees -- Africa; Refugees -- Government policy -- South Africa; Refugees -- Legal status, laws, etc. -- South Africa; Asylum, Right of -- South Africa